Effectiveness of the Beyond Good Intentions Program on Improving Dietary Quality Among People With Type 2 Diabetes Mellitus: A Randomized Controlled Trial - van der Velde, Laura A.; Kiefte-de Jong, Jessica C.; Rutten, Guy E.; Vos, Rimke C. (Frontiers in Nutrition, 2021)
Background and aims: An appropriate diet is an essential component of the management of Type 2 Diabetes Mellitus (T2DM). However, for many people with T2DM, self-management is difficult. Therefore, the Beyond Good Intentions (BGI) education program was developed based on self-regulation and proactive coping theories to enhance people’s capabilities for self-management. The aim of this study was to determine the effectiveness of the BGI program on improving dietary quality among a preselected group of people with T2DM after two-and-a-half years follow-up. Methods: In this randomized controlled trial, 108 people with T2DM were randomized (1:1) to the intervention (n=56) (BGI-program) or control group (n=52) (care as usual). Linear regression analyses were used to determine the effect of the BGI program on change in dietary quality between baseline and two-and-a-half years follow-up. In addition, potential effect modification by having a nutritional goal at baseline was evaluated. Multiple imputation (n=15 imputations) was performed to account for potential bias due to missing data. Results: According to intention-to-treat analysis, participants in the intervention group showed greater improvements in dietary quality score than participants in the control group (β=0.71; 95%CI: 0.09; 1.33) after follow-up. Having a nutritional goal at baseline had a moderating effect on the effectiveness of the BGI program on dietary quality (p-interaction=0.01), and stratified results showed that the favorable effect of the intervention on dietary quality was stronger for participants without a nutritional goal at baseline (no nutritional goal: β=1.46; 95%CI: 0.65; 2.27 vs. nutritional goal: β= -0.24; 95%CI: -1.17; 0.69). Conclusions: The BGI program was significantly effective in improving dietary quality among preselected people with T2DM compared to care as usual. This effect was stronger among participants without a nutritional goal at baseline. A possible explanation for this finding is that persons with a nutritional goal at baseline already started improving their dietary intake before the start of the BGI program. Future studies are needed to elucidate the moderating role of goalsetting on the effectiveness of the BGI program.